[Bataan Nuclear Plant '92 ; Guns and goons in Ternate, Cavite ; The filipinos of King and I [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
The government settles case on Bataan Nuclear Power Plant against Westinghouse Electric, s.A. outside the court. Looks into the killing of Ternate, Cavite Mayor Octavio Velasco. Probe Team's trip to Melbourne Australia to see the Australian production of Rodgers and Hammerstein's "The King and I."